Surgical vs Nonoperative Treatment for Lumbar Disk Herniation: The Spine Patient Outcomes Research Trial (SPORT): A Randomized Trial - Weinstein, James; Tosteson, Tor D.; Lurie, Jon D.; Tosteson, Anna N.A.; Hanscom, Brett; Skinner, Jonathan S.; Abdu, William A.; Hilibrand, Alan S.; Boden, Scott D.; Deyo, Richard A. (JAMA, 2006)
Lumbar diskectomy is the most common surgical procedure performed in the United States for patients having back and leg symptoms; the vast majority of the procedures are elective. However, lumbar disk herniation is often seen on imaging studies in the absence of symptoms1,2 and can regress over time without surgery.3 Up to 15-fold variation in regional diskectomy rates in the United States4 and lower rates internationally raise questions regarding the appropriateness of some of these surgeries.5,6 Several studies have compared surgical and nonoperative treatment of patients with herniated disk, but baseline differences between treatment groups, small sample sizes, or lack of validated outcome measures in these studies limit evidence-based conclusions regarding optimal treatment.7-12 The Spine Patient Outcomes Research Trial (SPORT) was initiated in March 2000 to compare the outcomes of surgical and nonoperative treatment for lumbar intervertebral disk herniation, spinal stenosis, or degenerative spondylolisthesis.13 The trial included both a randomized cohort and an observational cohort who declined to be randomized in favor of designating their own treatment but otherwise met all the other criteria for inclusion and who agreed to undergo follow-up according to the same protocol. This article reports intent-to-treat results through 2 years for the randomized cohort.